Purinoceptor modulation of noradrenaline release in rat tail artery: Tonic modulation mediated by inhibitory P-2Y- and facilitatory A(2A)-purinoceptors - Goncalves, J (1996)
1 The effects of analogues of adenosine and ATP on noradrenaline release elicited by electrical stimulation (5 Hz, 2700 pulses) were studied in superfused preparations of rat tail artery. The effects of purinoceptor antagonists, of adenosine deaminase and of adenosine uptake blockade were also examined. Noradrenaline was measured by h.p.l.c, electrochemical detection. 2 The A(1)-adenosine receptor agonist, N-6-cyclopentyladenosine (CPA; 0.1-100 nM) reduced, whereas A(2A)-receptor agonist 2-p-(2-carboxyethyl)phenelhylamino-5'-N-ethylcarboxamidoadenosine (CGS 21680; 3-30 nM) increased evoked noradrenaline overflow. These effects were antagonized by the A(1)-adenosine receptor antagonist, 8-cyclopentyl-1,3-dipropylxanthine (DPCPX; 20 nM) and the A(2)-adenosine receptor antagonist, 3,7-dimethyl-1-propargylxanthine (DMPX; 100 nM), respectively. The P-2Y-purinoceptor agonist, 2-methylthio-ATP (1-100 mu M) reduced noradrenaline overflow, an effect prevented by the P-2-purinoceptor antagonist, cibacron blue 3GA (100 mu M) and suramin (100 mu M). 3 Adenosine deaminase (2 u ml(-1)), DMPX (100 nM) and inhibition of adenosine uptake with S-(p-nitrobenzyl)-6-thioinosine (NBTI; 50 nM) decreased evoked noradrenaline overflow. DPCPX alone did not change noradrenaline overflow but prevented the inhibition caused by NBTI. The P-2Y-purinoceptor antagonist, cibacron blue 3GA (100 mu M) increased evoked noradrenaline overflow as did suramin, a nonselective P-2-antagonist. 4 It is concluded that, in rat tail artery, inhibitory (A(1) and P-2Y) and facilitatory (A(2A)) purinoceptors are present and modulate noradrenaline release evoked by electrical stimulation. Endogenous purines tonically modulate noradrenaline release through activation of inhibitory P-2Y and facilitatory A(2A) purinoceptors, whereas a tonic activation of inhibitory A(1) purinoceptors seems to be prevented by adenosine uptake.